Desenvolvimento territorial, políticas públicas e inovação social no Alto Jequitinhonha - MG - Oliveira, Allain Wilham Silva de [UNESP] (2015)
This analysis aims to contribute, in the scope of the rural development and territorial policies, for the reflection about the Rural and Territorial Development Program under the management of the Ministry of Agrarian Development (MAD), and the citizen territory under the management of the civil house. The spatial approach, a territory for the development, represents a plot with bond in the historical and social roofs, politics configurations and identities that plays a role still in analysis in Geography and in the Social Science. Thereby, one of the great debates nowadays, that it manifested as key element from it is called globalization, it is a matter of territoriality, the place and the identity or search for a local economic system that does not mean autarchy or displacement, but opening of new opportunities in the improvement of the institution with territorial basis. Thus, the first questions appear: Would the territorial development be a spatial adequacy of the system, backing to the westernization of places? Or it would be its contestation with affirmation of local identities? Therefore, would the territorialization proposed transform the space into a support only or a component for development? Or, it can be asked: Development in the territory or with the territory? Can public policies produce repossession or only affirmation of territoriality? The region chosen is the Jequitinhonha Valley, in Minas Gerais, known for low social indicators with a very little practiced familiar agriculture or not integrated in the market...